Penerapan Metode Weighted Moving Average (Wma) Pada Persediaan Barang Jadi Kopi Herbal Asy-Syifa Menggunakan Software Pom-Qm For Windows: Studi Kasus Pada UMKM HMS Herbal Tasikmalaya - Rizqi Insani; Arga Sutrisna; Ari Arisman (CV. Ulil Albab Corp, 2022)
HMS Herbal Tasikmalaya is a company that sells and manufactures various kinds of herbal products located on Jl. Panyingkiran no. 63 Singaparna. There are problems experienced by HMS Herbal Tasikmalaya, including inaccurate inventory, in this case Asy-Syifa Herbal Coffee. Inventories of goods often experience shortages and even empty when customers need these goods. Another problem that is often faced is the accumulation of goods in the store for a long period of time, because there are no purchases from customers. This study aims to predict inventory data in the future by using the Weighted Moving Average (WMA) forecasting method to minimize the occurrence of shortages and even vacancies (out of stock) and buildup (out of stock) inventory. The method used in this research is a descriptive method with a qualitative approach with data collection techniques through field research, namely interviews, documentation and library research related to the problems studied. The calculation analysis of this research uses the Weighted Moving Average (WMA) method with the help of POM-QM software for Windows. Forecasting analysis using the WMA method uses 8 weighting values ​​which produce inventory forecast data for the next period, namely 75 pcs. From the results of the analysis of the forecasting calculations using the WMA method, the MAD error value is 31,908, the MSE value is 1729,259, and the MAPE value is 35.46%.